Implementation of Play-Based Methods to Improve Football Passing Skills at SMPN 8 Seluas Bengkayang Regency - Supriadi, Idris; Ginting, Fajar Sharon; Effendi, Awang Roni; Wardhani, Rio (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. This research aims to improve passing skills in football among students of SMPN 8 Seluas, Bengkayang Regency. The researcher hopes that this study can be utilized by other researchers to enhance student learning in schools. Materials and Methods. The material provided focuses on passing using the inside of the foot in football, taught through a play-based method. This research employs a classroom action research method conducted in two cycles. The research subjects are 28 eighth-grade students, consisting of 20 males and 8 females. The instruments used in this study include measurement techniques and observation sheets. Results. The pre-cycle data results show that students' ability to perform passing using the inside of the foot had not yet reached the minimum mastery criterion of 75%. Specifically, 23 students (82.14%) did not meet the criterion, while only 5 students (17.85%) achieved it. Subsequently, instruction on inside-foot passing was provided through a play-based method. This had an impact on the passing skills results in football, as shown in the Cycle I test. Out of 28 students, 17 students (60.71%) achieved mastery, while 11 students (39.28%) did not. The researcher continued the study with Cycle II, applying the same method as in Cycle I. The results from Cycle II show that 23 students (82.14%) achieved mastery, while 5 students (17.85%) did not. Conclusions. ased on the research results above, it can be concluded that the play-based method can improve passing skills in football among eighth-grade students of SMP Negeri 8 Seluas, Bengkayang Regency